2019
DOI: 10.1111/caim.12340
|View full text |Cite
|
Sign up to set email alerts
|

Saying and doing: Social responsibility declared and applied

Abstract: The purpose of this work is to examine the relationships between and among firms' commitment to social responsibility, their declarations—or reporting—on their social responsibility, the application of social responsibility in the form of social innovation, and customer acceptance. A research model drawing on the attributes of stakeholder theory is tested using data collected from 355 firms. The findings indicate that firms with commitments to social responsibility are likely to report on their social responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 157 publications
(249 reference statements)
1
5
0
Order By: Relevance
“…The response rate for this study is 14.8%. Although this response rate is not as high as one might wish, it is still comparable with that of recent studies in innovation (e.g., Pollok et al, 2019; Sigurdsson & Candi, 2020) and provides sufficient statistical power for the testing of the study's hypotheses. Power calculations were based on a medium effect size and Type I error values ( α ) of .05.…”
Section: Methodssupporting
confidence: 79%
“…The response rate for this study is 14.8%. Although this response rate is not as high as one might wish, it is still comparable with that of recent studies in innovation (e.g., Pollok et al, 2019; Sigurdsson & Candi, 2020) and provides sufficient statistical power for the testing of the study's hypotheses. Power calculations were based on a medium effect size and Type I error values ( α ) of .05.…”
Section: Methodssupporting
confidence: 79%
“…For example, Carberry et al. (2019) and Sigurdsson and Candi (2020) both measured SI quantitatively from different perspectives rather than the SI process.…”
Section: Discussionmentioning
confidence: 99%
“…2019) identified various strategic considerations of social context and the influence each can have on social innovation. Firstly, a firm's commitment to social responsibility and its internal and external practices were identified as important factors in social innovation adoption (Altuna et al, 2015;Sigurdsson and Candi, 2020). For example, Carberry et al (2019) confirmed that "social movement activists" are very effective at fostering CSI.…”
Section: Corporate Social Innovationmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, aesthetics play a crucial role in satisfying consumers, as they appreciate designers who demonstrate creativity and a willingness to challenge design norms [25]. Various studies have evaluated the importance of aesthetics [24,[26][27][28]. However, symbolic design dimensions have received little attention [22].…”
Section: Design Elements and Value Continuationmentioning
confidence: 99%